Muatan Pendidikan Holistik dalam Kurikulum Pendidikan Dasar dan Menengah - Herry Widyastono (Jurnal Pendidikan dan Kebudayaan, 2012)
Holistic education is the education which develops all students potentials in harmony comprises intellectual, emotional, physical, social, esthetic, and spiritual potentials. This article is aimed at describing on whether or not there is the degree of holistic approach in education, particularly for the basic and secondary education. In addition, this describes its implementation at the schools within the basic and secondary education. The problems are formulated as follows 1) whether the basic and secondary education has already been regarded as holistic education?, 2) if yes, how its implementation at the schools concerned. This concludes that: 1) the basic and secondary curriculums have, in principle, been as holistic ones because its principles, reference, and procedure to develop the curriculum are in line with the definition, objective, and the principles which support to it. 2) The holistic education is not yet implemented comprehensively at the schools. In terms of its implementation it is, therefore, advisable that all teachers, while teaching in the classroom, should give the students to have ample opportunities to develop not only their cognitive domain, but their psychomotor and affective ones through active learning.